Current international flow cytometric practices for the detection and monitoring of paroxysmal nocturnal haemoglobinuria clones: A UK NEQAS survey. Issue 4 (18th April 2016) - Fletcher, Matthew; Whitby, Liam; Whitby, Alison; Barnett, David
Abstract : Background: Paroxysmal nocturnal haemoglobinuria (PNH) is a rare acquired genetic disorder, with an incidence of approximately 1.3 new cases per million population per year. Evidence from the UK National External Quality Assessment Service for Leucocyte Immunophenotyping (UK NEQAS LI) programme suggested major discrepancies on how PNH testing is undertaken. To investigate this we surveyed laboratories in the UK NEQAS LI PNH programme and report here the findings. Methods: A questionnaire was distributed to all centres registered in UK NEQAS LI flow cytometry programmes ( n  = 1587). Comprising several subsections, it covered the majority of clinical flow cytometric practices. Participants completed a general section and then the subsections relevant to their laboratory repertoire. One subsection contained 34 questions regarding practices in PNH clone detection. Results: A total of 105 laboratories returned results for the PNH section; the results demonstrated lack of consensus in all areas of PNH testing. Variation was seen in gating and testing strategies, sensitivity levels and final reporting of test results. Several incorrect practices were highlighted such as inappropriate antibody selection and failure to wash the red blood cells (RBCs) prior to analysis. Conclusion: Despite the availability of consensus guidelines there appears to be no agreement in the detection and monitoring of PNH. We found only fourteen centres using methods compatible with the International Clinical Cytometry Society guidelines. Of specific note we found that no two laboratories used the same method. This technical variation could lead to incorrect diagnoses, highlighting the need for better adoption and understanding of consensus practices. © 2016 International Clinical Cytometry Society